Respuesta :
Answer:
(x,y)=(1,-4)
Step-by-step explanation:
y=−7x+3
y=−x−3
(y=) −7x+3=−x−3
-7x+x=-3-3
-6x=-6
x=-6/(-6)
x=1
y=-7*1+3=-7+3=-4
(x,y)=(1,-4)
Answer:
[tex](x,y)= (1,-4)\\[/tex]
Step-by-step explanation:
We will solve it using the substitution method
Using Substitution method
Let [tex]y = -7x + 3[/tex] be equation 1 and [tex]y = -x - 3[/tex] be equation 2
putting value of y from equation 1 in equation 2 and further simplifying:
we get
[tex]-7x +3 = -x - 3\\-7x + x = -3 -3\\-6x =-6\\\\6x=6x\\x= 1[/tex]
Now put value of x i.e. [tex]x=1[/tex] in equation 1 and by further simplifying
[tex]y = -7x + 3\\y= -7(1) +3\\y= -7+3\\y=-4[/tex]
So the solution to the system is written as\[tex](x,y)= (1,-4)[/tex]